Positive End-expiratory Pressure and Postoperative Atelectasis: A Randomized Controlled Trial. (October 2019) - Östberg, Erland; Thorisson, Arnar; Enlund, Mats; Zetterström, Henrik; Hedenstierna, Göran; Edmark, Lennart
Abstract : Background: Positive end-expiratory pressure (PEEP) increases lung volume and protects against alveolar collapse during anesthesia. During emergence, safety preoxygenation preparatory to extubation makes the lung susceptible to gas absorption and alveolar collapse, especially in dependent regions being kept open by PEEP. We hypothesized that withdrawing PEEP before starting emergence preoxygenation would limit postoperative atelectasis formation. Methods: This was a randomized controlled evaluator-blinded trial in 30 healthy patients undergoing nonabdominal surgery under general anesthesia and mechanical ventilation with PEEP 7 or 9 cm H2 O depending on body mass index. A computed tomography scan at the end of surgery assessed baseline atelectasis. The study subjects were thereafter allocated to either maintained PEEP (n = 16) or zero PEEP (n = 14) during emergence preoxygenation. The primary outcome was change in atelectasis area as evaluated by a second computed tomography scan 30 min after extubation. Oxygenation was assessed by arterial blood gases. Results: Baseline atelectasis was small and increased modestly during awakening, with no statistically significant difference between groups. With PEEP applied during awakening, the increase in atelectasis area was median (range) 1.6 (−1.1 to 12.3) cm 2 and without PEEP 2.3 (−1.6 to 7.8) cm 2 . The difference was 0.7 cm 2 (95% CI, −0.8 to 2.9 cm 2 ; P = 0.400). Postoperative atelectasis for all patients was median 5.2 cm 2 (95% CI, 4.3 to 5.7 cm 2 ), corresponding to median 2.5% of the total lung area (95% CI, 2.0 to 3.0%). Postoperative oxygenation was unchanged in both groups when compared to oxygenation in the preoperative awake state. Conclusions: Withdrawing PEEP before emergence preoxygenation does not reduce atelectasis formation after nonabdominal surgery. Despite using 100% oxygen during awakening, postoperative atelectasis is small and does not affect oxygenation, possibly conditional on an open lung during anesthesia, as achieved by intraoperative PEEP. Abstract : Thirty patients undergoing nonabdominal surgery under general anesthesia were randomized to maintained (7 or 9 cm H2 O) or zero positive end-expiratory pressure before being given 100% oxygen for emergence preoxygenation. Postoperative atelectasis (assessed by computed tomography) was small with no effect on oxygenation, whether or not positive end-expiratory pressure was used during emergence.